The Role Of The Innovative Service Product In Achieving Community Development - نصور, ريزان; لايقة, يقين (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Some organizations working within the Syrian market seek to exploit the needs and desires imposed by the current crisis in order to achieve economic goals and reach societal development at the same time by creating new products of value to the organization and customers together. The research aimed to study the role of the innovative service product in achieving Community development in the Syrian private universities through a case study of Al-Manara University, and the study was based on the descriptive and analytical approach, and the data were collected by distributing the questionnaire to an intended sample of members of the educational and administrative staff, where the number of the studied sample reached 40 individuals during the second half of 2019. The researcher recommended increasing interest in opening new academic study branches in universities and focusing on innovative interactive education tools and increasing cooperation with NGOs to contribute to creating innovative ideas to provide service products in line with market requirements, especially during the current marketing crisis phase.